An accurate method for real-time chest compression detection from the impedance signal. (August 2016) - Kwok, Heemun; Coult, Jason; Liu, Chenguang; Blackwood, Jennifer; Kudenchuk, Peter J.; Rea, Thomas D.; Sherman, Lawrence
Abstract: Objective: Real-time feedback improves CPR performance. Chest compression data may be obtained from an accelerometer/force sensor, but the impedance signal would serve as a less costly, universally available alternative. The objective is to assess the performance of a method which detects the presence/absence of chest compressions and derives CPR quality metrics from the impedance signal in real-time at 1 s intervals without any latency period. Methods: Defibrillator recordings from cardiac arrest cases were divided into derivation ( N  = 119) and validation ( N  = 105) datasets. With the force signal as reference, the presence/absence of chest compressions in the impedance signal was manually annotated (reference standard). The method classified the impedance signal at 1 s intervals as Chest Compressions Present, Chest Compressions Absent or Indeterminate . Accuracy, sensitivity and specificity for chest compression detection were calculated for each case. Differences between method and reference standard chest compression fractions and rates were calculated on a minute-to-minute basis. Results: In the validation set, median accuracy was 0.99 (IQR 0.98, 0.99) with 2% of 1 s intervals classified as Indeterminate . Median sensitivity and specificity were 0.99 (IQR 0.98, 1.0) and 0.98 (IQR 0.95, 1.0), respectively. Median chest compression fraction error was 0.00 (IQR −0.01, 0.00), and median chest compression rate error was 1.8 (IQR 0.6, 3.3) compressions per minute. Conclusion: A real-time method detected chest compressions from the impedance signal with high sensitivity and specificity and accurately estimated chest compression fraction and rate. Future investigation should evaluate whether an impedance-based guidance system can provide an acceptable alternative to an accelerometer-based system.